Good laboratory practice: preventing introduction of bias at the bench - Macleod, Malcolm R.; Fisher, Marc; O'Collins, Victoria; Sena, Emily S.; Dirnagl, Ulrich; Bath, Philip M.W.; Buchan, Alistair; van der Worp, H. Bart; Traystman, Richard; Minematsu, Kazuo; Donnan, Geoffrey A.; Howells, David W. (American Heart Association Inc, 2009)
Background and Purpose—As a research community, we have failed to demonstrate that drugs which show substantial efficacy in animal models of cerebral ischemia can also improve outcome in human stroke.